The Role of Intercultural Education in Developing Critical Thinking Skills and Attitudes in Teacher Training - Uribe Hincapié, Richard Alonso (2025)
Comprehensive and contextualized teacher training is vital for transforming schools into institutions that equip students with the skills needed to comprehend, analyze, and engage both constructively and critically with the multicultural complexities of their environment. This study aims to investigate how intercultural training, specifically benefits educators in fostering critical thinking skills and attitudes to help them face the pedagogical and social realities of a multifaceted and evolving world, through a group of education majors at four universities in Medellín, Colombia. The study employed a qualitative methodology with an interpretative, phenomenological-hermeneutic framework. The data was derived from analysis of Educational Program Projects (PEPs), semi-structured interviews, and autobiographical narratives. Training teachers in critical thinking favorably impacts educational and pedagogical practices. The study emphasizes the need for teachers to acquire a diverse critical understanding of culture and the role of intercultural education in cultivating such competencies. Thus, future educators will strengthen their role as mediators who understand contextual needs and institutional discourse to enable their students to better navigate the educational and social challenges of the 21st century.